ANTIMICROBIAL ACTIVITY STUDY OF NEW QUINAZOLIN-4(3H)-ONES AGAINST STAPHYLOCOCCUS AUREUS AND STREPTOCOCCUS PNEUMONIAE - M. A. Samotrueva; A. A. Ozerov; A. A. Starikova; N. M. Gabitova; D. V. Merezhkina; A. A. Tsibizova; I. N. Tyurenkov (Фармация и фармакология (Пятигорск), 2021)
Quinazolin-4(3H)-one derivatives exhibiting a wide spectrum of a pharmacological activity, represent a promising class of substances used to obtain antibacterial agents, which is especially important in the context of the emergence of pathogenic microorganisms’ resistance to drugs used in medicine. It has been proved that compounds having a naphthyl radical in the molecule, as well as an amide group bound to the benzene ring as quinazolinone substituents, are characterized by a pronounced antimicrobial activity against Staphylococcus aureus and Streptococcus pneumoniae.The aim of the research is a primary microbiological screening of the in vitro antimicrobial activity of new quinazolin-4(3H)-one derivatives against Staphylococcus aureus and Streptococcus pneumoniae, as well as the assessment of the relationship between the pharmacological effect and the structural transformation of the substance molecule, lipophilicity and the possibility of forming resistance to them.Materials and methods. The experimental studies have been carried out using well-known nosocomial pathogens of infectious and inflammatory diseases Staphylococcus aureus and Streptococcus pneumoniae by a serial dilution method.Results. A compound containing a naphthyl radical in its structure, which contributes to an increase in the hydrophobicity of the substance and its solubility in the membrane of a bacterial cell, has a bacteriostatic effect against both Staphylococcus aureus and Streptococcus pneumoniae. A similar pharmacological effect is exhibited by a derivative with an amide group as a substituent of the quinazolinone nucleus linked to a phenyl radical, which probably contributes to an increase in the degree of binding to active sites of enzymes involved in the DNA replication, and protein synthesis. Obviously, the increased lipophilicity, which promotes better binding to the efflux protein, cannot serve as objective characteristics of the emergence possibility of the pathogen’s resistance to this substance.Conclusion. Among the synthesized compounds, the leading substances that exhibit an antimicrobial activity against Staphylococcus aureus and Streptococcus pneumonia, have been identified. The assessment of the chemical structure made it possible to substantiate their pharmacological action and draw conclusions about the possibility of developing resistance to it in microbial cells.